Characteristics of patients with motor functional neurological disorder in a large UK mental health service: a case–control study. Issue 3 (18th February 2020) - O'Connell, N.; Nicholson, T. R.; Wessely, S.; David, A. S.
Abstract: Background: Functional neurological disorder (FND), previously known as conversion disorder, is common and often results in substantial distress and disability. Previous research lacks large sample sizes and clinical surveys are most commonly derived from neurological settings, limiting our understanding of the disorder and its associations in other contexts. We sought to address this by analysing a large anonymised electronic psychiatric health record dataset. Methods: Data were obtained from 322 patients in the South London and Maudsley NHS Foundation Trust (SLaM) who had an ICD-10 diagnosis of motor FND (mFND) (limb weakness or disorders of movement or gait) between 1 January 2006 and 31 December 2016. Data were collected on a range of socio-demographic and clinical factors and compared to 644 psychiatric control patients from the same register. Results: Weakness was the most commonly occurring functional symptom. mFND patients were more likely to be female, British, married, employed pre-morbidly, to have a carer and a physical health condition, but less likely to have had an inpatient psychiatric admission or to receive benefits. No differences in self-reported sexual or physical abuse rates were observed between groups, although mFND patients were more likely to experience life events linked to inter-personal difficulties. Conclusions: mFND patients have distinct demographic characteristics compared with psychiatric controls. Experiences of abuse appear to be equally prevalent across psychiatric patient groups. This study establishes the socio-demographic and life experience profile of this understudied patient group and may be used to guide future therapeutic interventions designed specifically for mFND.